Cultural struggles in the lusofonia arena: Portuguese-speaking migrant musicians in Lisbon - Vanspauwen, Bart P. (Afrika Focus, 2013)
Approaching music as a point of social connection in the post-colonial city of Lisbon, where cultural entrepreneurs deploy the political concept of lusofonia, this study examines the ways in which local migrant musicians from Portuguese-speaking African countries (PALOP), as well as Brazil and East Timor, position themselves in this context. In general, the study shows that there is a lack of recognition of the contribution they make to the expressive culture of the Portuguese capital, and this is related to national preconceptions. Surprisingly, despite several existing coun- ter-discourses regarding lusofonia, all interviewed musicians do see some future relevance in this concept. They appeal to both supranational institutions and national governments, asking for structural support in order to promote and disseminate all the expressive culture of Portuguese-speaking African countries, indicating that the contribution of migrant musicians from these countries should be considered as an integral part of Portugal’s cultural expression and heritage. Key words: Lusofonia, Portugal, migrant musicians, cultural policy, postcolonialism